Aging and Aging-Related Diseases Mechanisms and Interventions (Advances in Experimental Medicine and Biology,, 2018)
This book provides an overview of recent advances in the study of aging and aging related diseases, discussing the topics at individual, organ, tissue, cell, and molecular levels. It also presents studies on the biomarkers of aging and anti-aging interventions. Aging has been becoming a global health problem. However it was not possible to determine aging as we usually diagnose a disease because there are few biomarkers for age estimation. Since ancient times, people have been seeking anti-aging substances and methods for achieving immortality, while the scientific study of aging has only existed for 100 years. This book appeals to researchers both in institutes and in pharmaceutical companies interested in further studies in this field.